Counsellees' perceptions of their therapeutic alliance with traditional healers - Salina Samion. (2008)
This research examines counsellees' perceptions of the nature of their therapeutic alliance with the traditional healers. It also explores the similarities and differences of the nature of alliance as compared with the counsellees' formal relationship with their counsellors. This research which involves individuals who have engaged the services of both counsellors and traditional healers explores the therapeutic relationship in terms of the three dimensions of alliance namely; goal, task and bond.